A comparison of the use of different swab materials for optimal diagnosis of amoebic gill disease (AGD) in Atlantic salmon (Salmo salar L.). Issue 11 (3rd September 2020) - Fernandez‐Senac, Carolina; Fridman, Sophie; Sokolowska, Jadwiga; Monaghan, Sean J.; Garzon, Teresa; Betancor, Monica; Paladini, Giuseppe; Adams, Alexandra; Bron, James E.
Abstract: Routine gill swabbing is a non‐destructive sampling method used for the downstream qPCR detection and quantitation of the pathogen Neoparamoeba perurans, a causative agent of amoebic gill disease (AGD). Three commercially available swabs were compared aiming their application for timelier AGD diagnosis (Calgiswab ® (calcium alginate fibre‐tipped), Isohelix ® DNA buccal and cotton wool‐tipped). Calcium alginate is soluble in most sodium salts, which potentially allows the total recovery of biological material, hence a better extraction of target organisms' DNA. Thus, this study consisted of (a) an in vitro assessment involving spiking of the swabs with known amounts of amoebae and additional assessment of retrieval efficiency of amoebae from agar plates; (b) in vivo testing by swabbing of gill arches (second, third and fourth) of AGD‐infected fish. Both in vitro and in vivo experiments identified an enhanced amoeba retrieval with Calgiswab® and Isohelix® swabs in comparison with cotton swabs. Additionally, the third and fourth gill arches presented significantly higher amoebic loads compared to the second gill arch. Results suggest that limiting routine gill swabbing to one or two arches, instead of all, could likely lead to reduced stress‐related effects incurred by handling and sampling and a timelier diagnosis of AGD.